Organic Greenhouse Container Herb Production in South Florida: Fertilizer and Potting Media - Danielle Treadwell; Kati Migliaccio; Teresa Olczyk; Yun Qian; Yuncong Li; George Hochmuth; Robert Hochmuth; Eric H. Simonne; Lance S. Osborne; Richard K. Sprenkel (EDIS, 2020)
Field production of organic crops, including herbs, in south Florida is a challenging task due to the subtropical climate and high number of pest and disease pressures. Thus, greenhouse production of organic herbs may provide an alernate to field production. However, there is little published information on selecting media and fertilizers for organic herb production in greenhouses in this climate. Greenhouse trials were conducted during the 2005 and 2006 growing season at the UF/IFAS Tropical Research and Education Center (TREC) in Homestead, Florida. The objectives of the project were to 1) compare several commercially available organic fertilizers for organic greenhouse production of container herbs and 2) compare two commercially available potting media for organic greenhouse production of container herbs. The two potting media (Fafard and Agro-Soils) did not result in significant differences in measured plant mass production, plant tissue nutrients, or leachate chemistry. However, some differences in plant production for basil and dill were identified among the different fertilizer treatments (Natural Safe, Perdue, Fertrell, and Control). These differ- ences were most notable for visual quality, fresh weight, and dry weight measurements. Evaluation of these parameters for basil and dill suggested that the two best fertilizers were Perdue and Fertrell. However, the differences in cost of each fertilizer and the study results suggest that Perdue is a more economic choice for organic herb production of basil and dill.